Discovering reflective-narrative: constructing experience in the Deweyan guide for reflective practice. Issue 2 (4th March 2022) - Greenberger, Scott W.; Maguire, Kelly R.; Martin, Cheryl L.; Chavez, Tara E.; Delgado, Gina
ABSTRACT: This article provides an explanatory supplement for authors to more thickly describe their experience when using the published Guide for Reflective Practice (GRP). As members of the reflective practice laboratory that created the GRP, we recognized the need to provide stronger theoretical justification and practical instructions for the activity/project description section of the guide. The result of our inquiry was a reworking of the activity/project description section and renaming it reflective-narrative . John Dewey's theory of experience and Clandinin and Connelly's three-dimensions of narrative space were used to develop the instructions for writing a reflective-narrative. There is also discussion on how to ensure quality and rigor in writing such a narrative. We recommend creating additional instructional supplements for the GRP. We also discuss our plans to facilitate reflective writing retreats to train new faculty on writing a reflective-narrative and engaging in reflective practice.